Evaluating the role of citizen science in the context of human-wildlife conflict management - Adams, Morgan, author; Teel, Tara, advisor; Vaske, Jerry, committee member; Benson, Delwin, committee member (Colorado State University. Libraries, 2014)
This thesis presents two manuscripts that explored the potential of citizen science programs to be utilized in urban centers that are experiencing heightened rates of human-wildlife conflict (HWC). In particular, we focused on human-coyote conflicts, which are an emerging problem in many cities throughout North America. Recent reports have shown that while coyotes typically pose a minimal threat to people, attacks on humans have recently escalated. Certain traditional methods such as lethal control for dealing with human-coyote conflict, and HWC more broadly, are increasingly considered unacceptable to the public, creating a need for management authorities to consider other alternatives. Citizen science, a method in which members of the public contribute to real-world research studies, is one tool that could be considered, as citizen science is thought to be a valuable mechanism for increasing citizens' knowledge of ecological systems and the scientific process, and engaging them in resource management. The overall purpose of this thesis was to determine the motivations and characteristics of citizen science participants and evaluate if involvement in these programs can in fact lead to desired changes in participant understanding and subsequent behavior, therefore offering a useful approach for assisting with HWC management. The purpose of the first paper was to evaluate the potential for a citizen science program called Coyote Watch to change participant understanding and subsequent behavior in the context of human-coyote conflict in the Denver Metro Area (DMA) of Colorado. Our first objective was to assess the effects of the program over time on participants' attitudes, beliefs, behavioral intentions, and knowledge regarding coyotes. Our second objective was to explore the broader impacts of the program, including the extent to which participants used their program education and observation experiences to take action in their communities to prevent and manage conflict with coyotes. Data were collected using a mixed methods approach, including on-site and online surveys and interviews that were administered to new and previously trained volunteers of Coyote Watch. Results indicated that participation in Coyote Watch is positively affecting volunteers in terms of how they relate to and think about coyotes and coyote-related issues in their communities. Qualitative data from open-ended survey questions and interviews corroborated quantitative findings and demonstrated that the program is not only providing participants with enhanced knowledge of coyotes and their ecology, but it is also empowering some of these individuals to take action to prevent and manage conflicts with coyotes. The second paper focused on understanding the characteristics of citizen science volunteers with the intent of being able to inform the development and marketing of future programs in an HWC context. We had three objectives for this case study investigation:1) assess volunteers' motivations for joining Coyote Watch and subsequently determine whether these motivations were similar to or different from those identified by previous research on volunteerism in environmental projects, 2) explore the extent to which volunteers represented the DMA resident population as a whole with respect to key demographic characteristics, and 3) compare Coyote Watch participants to respondents from a larger DMA resident survey in regards to their coyote-related attitudes, beliefs, and behavioral intentions. Data collection was accomplished using on-site and online surveys administered to Coyote Watch volunteers and through mailed and online surveys for the larger DMA study. Results indicated that volunteers often had more than one motivation for joining the program, such as an enjoyment of wildlife, a desire to participate in research and to inform others people about coyotes and coyote issues, and that they did in fact share some of the demographic characteristics of DMA residents as a whole. However, we also noted certain demographic differences between volunteers and the resident population, particularly with respect to gender, age, and education. Furthermore, results determined that Coyote Watch volunteers differed in some respects from respondents to the larger DMA-wide resident survey in their attitudes, beliefs and behavioral intentions regarding coyotes, as the volunteers had more positive general attitudes regarding coyotes, they were more likely to agree with advantages of having coyotes in their areas, and they were more likely to perform certain actions around their homes in order to reduce conflict with coyotes. As a whole, these studies demonstrated that many individuals who participated in Coyote Watch expressed a better understanding of coyote behavior and an ability to use their education to take measures to prevent and manage conflict. Additionally, these individuals may be similar to other residents in the DMA, but they tend to feel more positively toward coyotes and they are willing to take more steps to decrease negative interactions with coyotes. Thus, our findings suggest that citizen science programs may offer an innovative alternative method to augment traditional forms of HWC mitigation in urban settings.